The Role of The School Committee In Improving The Quality of Education In Banda Aceh City State Junior High Schools - Akmaluddin Akmaluddin (Dinasti Publisher, 2024)
This research aims to describe the role of school committees in improving the quality of education in Banda Aceh City State Junior High Schools. This research uses a qualitative method with a descriptive approach. Subjects in this research included school principals, school committees, teachers and deputy principals for curriculum. The location of this research is the Banda Aceh State Junior High School. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The research results show that the role of the school committee includes the planning, implementation and evaluation stages. The school committee has three main functions, namely as a controller of educational quality planning, such as planning educational programs at Banda Aceh State Junior High Schools. Apart from that, the school committee always supervises the implementation of every planned activity at the Banda Aceh State Junior High School. The committee's role also includes monitoring educational output results. However, the school committee at the Banda Aceh State Junior High School is not involved in controlling the results of the final exam, but only participates in supervising the implementation of the student's final exam.